1999
DOI: 10.1590/s1516-14391999000300002
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of microstructures

Abstract: Structure is at the heart of the materials science paradigm connecting processing with properties. In the hierarchy of structures that exist in materials microstructure offers the richest variety of structural arrangements. This variety is often conveniently accessible, e.g., simply by heat treatment or mechanical deformation. Exploration of the relation between properties and microstructure serves to establish a target range of microstructural states that will perform. In order to attain a target microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…One important aspect of the microstructure is the size of the grains and its influence on the properties. Thus, in order to design the grain size and restrict grain growth, microstructural engineering has become of fundamental importance [ 4 ]. The boundary between one grain and its neighbours (grain boundary) is a defect in the crystal structure and is associated with a certain amount of energy.…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect of the microstructure is the size of the grains and its influence on the properties. Thus, in order to design the grain size and restrict grain growth, microstructural engineering has become of fundamental importance [ 4 ]. The boundary between one grain and its neighbours (grain boundary) is a defect in the crystal structure and is associated with a certain amount of energy.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,17,18) The average and the product of the two principal curvatures are given by where H and K denote the mean and Gaussian curvatures, respectively. The mean curvature is related to the composition at the interface of a two-phase alloy; thus, it is an important parameter in microstructure evolution.…”
Section: Quantitative Analysis Of 3d Microstructuralmentioning
confidence: 99%
“…In materials science, it is well-known that morphology of microstructures plays a vital role on properties of materials. 2,3) For example, geometrical arrangement of martensite in a martensite-ferrite dual-phase (DP) steel affects the deformation and fracture behavior of the steel in addition to the yield strength ratio between martensite and ferrite, 4) the volume fraction of martensite, 5,6) and grain size. 6,7) It has been reported that a work-hardening rate becomes larger and fracture mode becomes brittle when ferrite is surrounded by honeycombed martensite, whereas uniform elongation becomes higher when ferrite is accompanied by dispersed martensite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the basic postulates of stereology [9][10][11], the surface and volume distribution of a measured/determined morphological parameter are mutually equal in the first approximation. According to the basic postulates of stereology [9][10][11], the surface and volume distribution of a measured/determined morphological parameter are mutually equal in the first approximation.…”
mentioning
confidence: 99%